The dissociating effects of fear and disgust on multisensory integration in autism: evidence from evoked potentials - Stefanou, Maria Elena; Dundon, Neil M.; Bestelmeyer, Patricia E. G.; Biscaldi, Monica; Smyrnis, Nikolaos; Klein, Christoph (Frontiers in Neuroscience, 2024)
Background Deficits in Multisensory Integration (MSI) in ASD have been reported repeatedly and have been suggested to be caused by altered long-range connectivity. Here we investigate behavioral and ERP correlates of MSI in ASD using ecologically valid videos of emotional expressions. Methods In the present study, we set out to investigate the electrophysiological correlates of audiovisual MSI in young autistic and neurotypical adolescents. We employed dynamic stimuli of high ecological validity (500 ms clips produced by actors) that depicted fear or disgust in unimodal (visual and auditory), and bimodal (audiovisual) conditions. Results We report robust MSI effects at both the behavioral and electrophysiological levels and pronounced differences between autistic and neurotypical participants. Specifically, neurotypical controls showed robust behavioral MSI for both emotions as seen through a significant speed-up of bimodal response time (RT), confirmed by Miller’s Race Model Inequality (RMI), with greater MSI effects for fear than disgust. Adolescents with ASD, by contrast, showed behavioral MSI only for fear. At the electrophysiological level, the bimodal condition as compared to the unimodal conditions reduced the amplitudes of the visual P100 and auditory P200 and increased the amplitude of the visual N170 regardless of group. Furthermore, a cluster-based analysis across all electrodes revealed that adolescents with ASD showed an overall delayed and spatially constrained MSI effect compared to controls. Conclusion Given that the variables we measured reflect attention, our findings suggest that MSI can be modulated by the differential effects on attention that fear and disgust produce. We also argue that the MSI deficits seen in autistic individuals can be compensated for at later processing stages by (a) the attention-orienting effects of fear, at the behavioral level, and (b) at the electrophysiological level via increased attentional effort.